Sustainability criteria of apicultural industry: evidence from Iran - Mohammad Kazem Rahimi (Taylor & Francis Group, 2020)
This study aimed to determine the sustainability criteria of the beekeeping industry in Iran, which was performed using three-stage classical Delphi technique. The participants were 32 experts in beekeeping industry who were purposefully selected using the snowball sampling method. The criteria identified, after three Delphi stages, consisted of 70 items, which were categorized into 13 general criteria and into four economic, environmental, social, and institutional dimensions. The general criteria were presented in the form of a conceptual model, including: farmers’ environmental behavior quality, beekeepers' environmental behavior quality, the quality of marketing and sales of beekeeping productions, productivity and performance improvement, amount of monetization from pollinations' right, the amount of monetization of byproducts and value added, employment rate and job stability, the level of social development of stakeholders, the quality of the role-playing of non-governmental stakeholders, the quality of extension and education new sciences and technologies to stakeholders, comprehensiveness of laws and programs, quality of role-playing of stakeholder non-governmental organizations, and the quality of the roleplaying of governmental institutions stakeholder. Using them, a comprehensive perception of the necessary criteria for the sustainability of Iran's beekeeping industry can be obtained and a comprehensive program can be designed for its implementation.